Lightweight privacy protection data auditing scheme for regenerating-coding-based distributed storage - Guangjun LIU; Wangmei GUO; Jinbo XIONG; Ximeng LIU; Changyu DONG (Tongxin xuebao)
To reduce the security implementation cost of the outsourcing data audit mechanism for the regenerating-coding-based distributed storage systems, an orthogonal algebraic coding method was put forward to construct a lightweight privacy-preserving audit scheme based on linear homomorphic authentication.The homomorphic authentication tags were generated with the orthogonalization between the file encoded data and the private secret key vector, and the privacy protection of the auditing response message was achieved by using the random masking that was constructed by randomizing the orthogonal basis vectors of the specific sub-vector of the user’s secret key.The work realized the effective integration of algebraic coding, privacy protection, and security auditing.Theoretical analysis shows that the proposed scheme can realize the information-theoretic security in the regenerating-coding-based storage applications.Compared with the existing works, the proposed scheme is of low computational complexity and communication overhead, and better performance advantages.